Homeland security the possible, probable, and perils of information technology. - Kun, L.G.
Information technology is a key component in both defending against and aiding terrorism threats. The author considers the background in making progress with technology, bioterrorism and other forms of terrorism, cybersecurity - national (and global) critical information infrastructure protection, and the possibility of the establishment of a new department, the Department of (National) Homeland Security. He concludes that, more than ever, coordination, cooperation, and integration become a fundamental must in order to optimize our resources, which calls for standardization and interoperability of resources.
Keywords: Department of Homeland Security; Bioterrorism; Cooperation; Coordination; Cybersecurity; Global critical information infrastructure protection; Homeland security; Information technology; Integration; Interoperability of resources; National critical information infrastructure protection; Standardization; Terrorism threats